Climate Change and Community Resilience 2021
DOI: 10.1007/978-981-16-0680-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting and Rural Livelihoods in Nepal

Abstract: Springs are drying and rainfall patterns are changing in the Himalayas, resulting in water scarcityfor agriculture. We examine the adoption of rainwater harvesting, a technology that has been recently re-designed and re-introduced to farmers in Nepal, as a climate change adaptation strategy in mountain farming. Using farm household surveys, we examine the impact of the adoption of rainwater harvestingon farm income and profitability. The adoption of the technology is mostly driven by external support such as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…In particular, individual cisterns enable water supply at the household level (St. Eustatius), while isolated tanks connected to ponds/tanks and reservoirs enable irrigated agriculture and livestock production (Sri Lanka). Technologies for RWH are part of collective memory in many cultures, but their large-scale productive exploitation is yet to be popularized [14,[103][104][105]. For example, Kattel and Nepal [14] acknowledged that "harvesting rainwater for animals is an old-age tradition in the hills of Nepal but rainwater harvesting for agriculture is relatively a new phenomenon".…”
Section: The Future Water Management In Feutapmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, individual cisterns enable water supply at the household level (St. Eustatius), while isolated tanks connected to ponds/tanks and reservoirs enable irrigated agriculture and livestock production (Sri Lanka). Technologies for RWH are part of collective memory in many cultures, but their large-scale productive exploitation is yet to be popularized [14,[103][104][105]. For example, Kattel and Nepal [14] acknowledged that "harvesting rainwater for animals is an old-age tradition in the hills of Nepal but rainwater harvesting for agriculture is relatively a new phenomenon".…”
Section: The Future Water Management In Feutapmentioning
confidence: 99%
“…Technologies for RWH are part of collective memory in many cultures, but their large-scale productive exploitation is yet to be popularized [14,[103][104][105]. For example, Kattel and Nepal [14] acknowledged that "harvesting rainwater for animals is an old-age tradition in the hills of Nepal but rainwater harvesting for agriculture is relatively a new phenomenon". As for Tanzania, large water harvesting ponds for agricultural purposes were common practices, with similar features from region to region, and even local names exist such as majaluba/ndiva [106].…”
Section: The Future Water Management In Feutapmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover with increased temperature, warm days and nights, and heat waves, it is likely that seasonal drought will also increase (Dahal et al, 2018). Currently, the majority of the hilly communities (85%) depend on rainfed agriculture (Kattel and Nepal, 2022). A similar case was observed in the districts selected for the FGDs.…”
Section: Food Insecurity and Malnutrition Under Climate Changementioning
confidence: 77%
“…Such tree plantations not only re-strengthen the embankments but also provide additional benefits such as carbon sequestration, greenery promotion, fuelwood production, and ecological balance (Pandey, 2016), which in turn helps local communities in recovering from climate change impacts (Udayashankara et al, 2016). Kattel & Nepal (2022) reported that local people are practicing rainwater harvesting techniques and the establishing conservation ponds to adapt to water scarcity. Nepal disaster report showed that rainfall pattern is changing, and drought periods are increasing throughout the country (GoN/MoHA, 2019).…”
Section: Adaptation Measures Practiced By Local Communitiesmentioning
confidence: 99%